Infant Distress in a Food Delay Task Changes With Development and Predicts Amount Consumed - Stein, Sara F.; Riley, Hurley O.; Kaciroti, Niko; Rosenblum, Katherine L.; Sturza, Julie M.; Gearhardt, Ashley N.; Grogan-Kaylor, Andrew C.; Lumeng, Julie C.; Miller, Alison L. (Frontiers in Nutrition, 2022)
Objective Eating behavior regulation emerges during early development and involves general self-regulation (emotional, behavioral), appetite regulation (homeostatic metabolic need) and appetite self-regulation (including both Bottom-Up Food Approach and Bottom-Up Food Avoidance and top-down purposeful self-control of eating). Limited research has investigated developmental trajectories of the regulation of eating behavior before the preschool years. The current study used a novel food delay task to assess infant distress as an early emerging marker of eating behavior regulation constructs across early infancy and examine associations with amount of milk consumed. Method Mother-infant dyads (n = 179) completed the Ability to Delay Gratification for Food in Infants Task (ATDG-FIT) at 2 weeks, 8 weeks, and 16 weeks of age. The ATDG-FIT required infants to wait before being fed while their bottle was present, but not accessible (3-min Pre-Feeding Delay). After this, the infant was fed for 1 min, then the feeding was paused for 30 s (Mid-Feeding Delay). Infant distress was coded during each feeding delay period and the amount of milk consumed was measured. Results The mean proportion of distress during the Pre-Feeding Delay period decreased from 8 to 16 weeks of age (F(2,230) = 15.02, p < 0.001), whereas the mean proportion of distress during the Mid-Feeding Delay increased from 2 to 8 weeks of age (F(2,230) = 27.04, p < 0.001). There was a positive interaction between distress during Mid-Feeding Delay and infant age predicting the amount consumed in the protocol (ß = 0.30, p = 0.022), suggesting that the association between distress during this part of the task and amount consumed strengthens as infants get older. Conclusion The ATDG-FIT may be an effective method to assess emerging eating behavior regulation constructs during early infancy.